PENGGUNAAN SERBUK KAYU SEBAGAI PENGGANTI AGREGAT KASAR PADA CAMPURAN BETON - sudirman; vike itteridi (JURNAL ILMIAH BERING'S, 2019)
In the modern era construction in the field of construction shows a very rapid development, thus demanding more innovative concrete technology. The purpose of this study was to determine the effect of partial replacement of split aggregates with wood powder and the addition of NaOH with different variations to specific gravity and compressive strength of concrete, to achieve specific gravity and compressive strength in concrete. The method used in this study is the experimental method, which is held a direct experiment to get a desired result. Testing of mechanical properties of concrete was performed at ages 3, 14, and 28 days for concrete weight test and concrete compressive strength. Based on the results of the study can be concluded: There is a negative influence of variation of partial replacement of coarse aggregates with wood powder and the addition of NaOH to the compressive strength of the concrete. The results of the specific gravity test indicate that the more use of wood powder, the smaller the specific gravity. Based on the results of weight testing the concrete has decreased an average of 10.27% for BCN 5% and 21.20% for 10% BCN, while the compressive strength of 45.28% for BCN 5% and 78.72% for 10% BCN.